2016
DOI: 10.4314/ahs.v16i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of pre-eclampsia in women living in Makole Ward, Dodoma, Tanzania

Abstract: Background: Pre-eclampsia is a hypertensive disorder specific to pregnancy responsible for significant maternal morbidity and mortality in Africa. The majority of deaths related to pre-eclampsia could be avoided with timely and effective care. "Phase one delays" arise because of lack of knowledge. Objectives: This study aimed to assess the knowledge levels of women living in Makole ward, comparing respondent subgroups with different demographic characteristics. It also aimed to compare knowledge levels in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 10 publications
9
25
3
1
Order By: Relevance
“…The results of the current study showed that 62.1% had inadequate knowledge about preeclampsia and eclampsia. The results of this study differ with the ndings of previous work done in Makole Dodoma [ 12 ]which revealed that 41% of the respondents had low knowledge. This difference might be due to the geographical location where study was conducted as the current study conducted in Rural while the previous conducted in Urban, also it could be due to the differences in study population as the current study dealt with expecting couples both pregnant women and their male partners while the previous study focused mainly on pregnant women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the current study showed that 62.1% had inadequate knowledge about preeclampsia and eclampsia. The results of this study differ with the ndings of previous work done in Makole Dodoma [ 12 ]which revealed that 41% of the respondents had low knowledge. This difference might be due to the geographical location where study was conducted as the current study conducted in Rural while the previous conducted in Urban, also it could be due to the differences in study population as the current study dealt with expecting couples both pregnant women and their male partners while the previous study focused mainly on pregnant women.…”
Section: Discussioncontrasting
confidence: 99%
“…Knowledge on preeclampsia and eclampsia was measured by nominal scale involved 38 items on knowledge with yes/no answers which were then converted into correct and incorrect. Then one score for each correct answer and zero score for each wrong answer(Savage & Hoho, 2016). Principal component analysis was done to analyze knowledge.…”
mentioning
confidence: 99%
“…In Malaysia, a study by Teng and Keng found only 18.4% of women to have adequate knowledge of PE [27]. Other studies by Savage and Hoho [25] and Eze et al [26] reported that 59% and 60% of Tanzanian women had inadequate knowledge of PE, respectively. Evidence indicates that adequate understanding of a disorder contributes to its prevention, control and management because patients' knowledge regarding a disease positively influenced patient compliance to treatment and help abate complications associated with the disease [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Investigator-administered validated well-structured questionnaire was used to collect data from all enrolled participants. The questionnaire was designed by reviewing previous studies of similar objectives [6,[24][25][26][27], after which experts consultation was sought to ascertain its validity in public health perspective. Required modifications were made and the questionnaire was administered in the language the participants understand.…”
Section: Questionnaire Administration and Data Collectionmentioning
confidence: 99%
“…For this to be achieved, there is the need to assess the baseline knowledge of PE, especially among high risk group such as pregnant women. Previous studies in the US [24] and a few countries in Africa [25][26][27] indicate that the knowledge of PE among women is generally low. However, there is currently no study that evaluates the knowledge of PE in Ghana.…”
Section: Introductionmentioning
confidence: 99%